A New Wave of COVID-19 in 2021 with Unique Genetic Characters - Present Global Scenario and Beholding Onwards - Mukherjee, Sukhes; Ray, Suman K. (Infectious Disorders - Drug Targets, 2022)
After the first report of a coronavirus-associated pneumonia outbreak in December 2019, the virus SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) that causes the infection/disease (COVID-19) has developed into a pandemic, with >100 million people infected in over 210 countries along with two million people deceased from COVID-19 till today. Coronaviruses are positivestranded RNA viruses having restricted RNA polymerase proofreading ability thus it is very genetically susceptible to mutation. The evolution of SARS-CoV-2 from a single-point zoonotic introduction in Wuhan in November or December 2019 was widely expected, and viral sequence surveillance was developed as a result. When the first sequence of SARS-CoV-2 was released, a race to develop vaccines started, and several vaccines are now used worldwide. Independent SARS-CoV-2 lineages have recently been identified in the UK (B.1.1.7), Brazil (P.1), South Africa (B.1.351), and India (B.1.617). The recent appearance of several SARS-CoV-2 variant strains has shattered faith in the modern generation of vaccines' ability to provide enduring defense against infection. The risk of escaping natural and induced immunity has encouraged an urgency to comprehend the implications of these improvements, as well as a drive to develop new approaches to combat SARS-CoV-2 variants.
Keywords: B.1.617